2005
DOI: 10.1111/j.1365-2893.2005.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of thymosin alpha‐1 in Japanese patients with chronic hepatitis B; results from a randomized clinical trial

Abstract: Thymalfasin (thymosin alpha-1; Talpha1) is a 28-amino acid polypeptide that has shown efficacy in the treatment of chronic hepatitis B virus (HBV) infection. The objective of this study was to evaluate the long-term, dose-related efficacy and safety of Talpha1 treatment in chronic hepatitis B patients with positive HBV-DNA and abnormally high alanine aminotransferase (ALT) levels. A total of 316 patients were randomized to receive either 0.8 or 1.6 mg of Talpha1 monotherapy for 24 weeks. At the end of the 72-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 30 publications
1
38
0
2
Order By: Relevance
“…Among adverse events possibly or probably related to thymalfasin, most were mild and resolved without sequelae, and only one (nipple pain) occurred in 10% or more of thymalfasin-treated patients. These results are consistent with those of previous clinical studies, in which thymalfasin has been shown to have an excellent safety profile [32,[45][46][47][48]. When evaluating new agents for HCC, it is crucial to determine that they do not worsen outcomes and survival due to associated toxicity, compared with placebo or existing treatments [49,50].…”
Section: Discussionsupporting
confidence: 87%
“…Among adverse events possibly or probably related to thymalfasin, most were mild and resolved without sequelae, and only one (nipple pain) occurred in 10% or more of thymalfasin-treated patients. These results are consistent with those of previous clinical studies, in which thymalfasin has been shown to have an excellent safety profile [32,[45][46][47][48]. When evaluating new agents for HCC, it is crucial to determine that they do not worsen outcomes and survival due to associated toxicity, compared with placebo or existing treatments [49,50].…”
Section: Discussionsupporting
confidence: 87%
“…It has since been accepted as the best treatment option for patients who have exhausted or are not amenable to more conservative medical or surgical therapies. TP is considered a therapy of last resort because it is associated with significant long-term metabolic effects [19], with all patients becoming dependent on exogenous insulin to maintain glucose homeostasis [31]. A summary of these findings is provided in Table 1.…”
Section: History Of Pancreatectomy As Treatment For Pancreatitismentioning
confidence: 99%
“…However, total pancreatectomy alone has been shown to have significant morbidity and mortality [17]. It results in total pancreatic endocrine and exocrine deficiency associated with a variety of deleterious metabolic complications including those directly related to postsurgical diabetes [18,19]. Gall, et al reported long term follow up in 117 patients who underwent total pancreatectomy for chronic pancreatitis reporting 19.1% mortality at 6.5 years with many late deaths caused by hypoglycemia [20].…”
Section: Promises In Endocrine Replacement Therapy Using Islet Transpmentioning
confidence: 99%
“…HBV genotype B responded to therapy better than genotype C (52% vs. 24%, P = 0.036) [67]. A study of 316 Japanese patients with HBeAg-positive chronic hepatitis B treated with either 0.8 or 1.6 mg of thymosin a 1 six times a week for the first 2 weeks and then twice a week for a further 22 weeks showed HBeAg seroconversion in 18.8% and 21.5% at 48 weeks after the end of treatment for the 0.8 and 1.6 mg doses, respectively [68]. In this study, 95% of the patients were genotype C and an HBeAg seroconversion rate of 21.5% was similar to 24% in a study of Taiwanese patients infected with genotype C [67,68].…”
Section: Thymosin a 1 In Chronic Hepatitis Bmentioning
confidence: 99%
“…A study of 316 Japanese patients with HBeAg-positive chronic hepatitis B treated with either 0.8 or 1.6 mg of thymosin a 1 six times a week for the first 2 weeks and then twice a week for a further 22 weeks showed HBeAg seroconversion in 18.8% and 21.5% at 48 weeks after the end of treatment for the 0.8 and 1.6 mg doses, respectively [68]. In this study, 95% of the patients were genotype C and an HBeAg seroconversion rate of 21.5% was similar to 24% in a study of Taiwanese patients infected with genotype C [67,68]. A meta-analysis including 353 patients from five trials showed that the odds ratios for virological response to thymosin a 1 at the end of treatment and 6 and 12 months post-treatment were 0.56 (0.2-1.52), 1.67 (0.83-3.37), and 2.67 (1.25-5.68), respectively, with a significantly increasing virological response over time after thymosin therapy [69].…”
Section: Thymosin a 1 In Chronic Hepatitis Bmentioning
confidence: 99%